The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cosmetics7020031
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy by Diaryl-Porphyrins to Control the Growth of Candida albicans

Abstract: Candida albicans is an opportunistic pathogen that often causes skin infections such as oral thrush, nail fungus, athlete’s foot, and diaper rash. Under particular conditions, C. albicans alters the natural balance of the host microbiota, and as a result, the skin or its accessory structures lose their function and appearance. Conventional antimycotic drugs are highly toxic to host tissues, and long-lasting drug administration induces the arising of resistant strains that make the antimycotic therapy ineffecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…Moreover, the eukaryotic microorganism Candida albicans showed to be sensitive in the dark to most cationic and dicationic diaryl-porphyrins tested in this study, irrespective of Soret band height [32]. Cormick reported that tri-and tetracationic porphyrins were more tightly bound to C. albicans cells than anionic porphyrins, supporting the requirement of positive charge on porphyrins to promote the electrostatic interaction with the yeast cell wall [41].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Moreover, the eukaryotic microorganism Candida albicans showed to be sensitive in the dark to most cationic and dicationic diaryl-porphyrins tested in this study, irrespective of Soret band height [32]. Cormick reported that tri-and tetracationic porphyrins were more tightly bound to C. albicans cells than anionic porphyrins, supporting the requirement of positive charge on porphyrins to promote the electrostatic interaction with the yeast cell wall [41].…”
Section: Discussionsupporting
confidence: 63%
“…A panel of novel diaryl-porphyrins, synthetized by our group and previously tested as antimicrobials [33] antifungals [32] and antitumorals [31,34], was investigated for anti-Pseudomonas activity (Table 1). The neutral and asymmetrical P1 and P2 bear in mesopositions (positions 5 and 15) a pentafluorophenyl group, associated with a C4 or C8 para-bromoalkyloxy-phenyl group, respectively.…”
Section: Panel Of Diaryl-porphyrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed on all the cell lines tested as previously described 52 with minor modifications. Briefly, according to the growth profiles previously defined for each cell line, adequate numbers of cells were plated in each well of a 96-well plate in 0.1 mL of complete culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…After overnight incubation at 37 °C, coverslip glasses were irradiated under light at 520 nm for 2 h in a humid chamber. Upon irradiation, adherent cells were stained for 30 min with 2 μM fluorochrome 4,4-difluoro-1,3,5,7-tetramethyl-8-(2-methoxyphenyl)-4-bora-3a,4a-diaza-s-indacene [26]. Then, the coverslips were transferred on microscope glass slides for confocal microscopy analysis.…”
Section: Photoinactivation Induced By Micelle-coated Glassmentioning
confidence: 99%